A Shibboleth upon their Tongues: Early English /r/ revisited - Gąsiorowski, Piotr (Adam Mickiewicz University, 2006)
This article discusses the pronunciation of the rhotic phoneme /r/ in early English. The traditional belief that the dominant pronunciation in Old and Middle English was [r] (an apical trill) is still supported by some authors, but there is growing consensus that there was a fairly wide range of /r/ realisations already in early Germanic, and that the pronunciation of /r/ in Old English was about as variable as it is in present-day English. The article defends this view and goes a step further, suggesting that the modern distribution of variant rhotic pronunciations in British English reflects to some extent the distribution of very similar sounds in Old English.